(untitled) (Baghdad Science Journal, 2014)
Five different bacterial isolates [ Vibrio cholera (Ogawa) , Vibrio cholera (Inaba) , Salmonella typhi , Salmonella paratyphi and ? Salmonella typhimurium ] were obtained from the Central Health Laboratory . Both sensitivity tests (MIC , MBC and wells method ) against these bacteria were performed by using the aqueous of leaves extract of Marjoram plant. The results cleared that the values of MIC for Vibrio cholera serotypes Ogawa and Inaba were 100 mg/ml , while the value of MBC was 200 mg/ml. The value of the Inhibition zone at 100 mg /ml concentration for both Ogawa and Inaba were 13 mm and 9 mm respectively. Our results showed that the three types of Salmonella didn’t show any inhibition zone at 200 mg/ml .